PENGGUNAAN BAHASA INDONESIA PADA GENERASI MILENIAL DI MEDIA SOSIAL: SEBUAH KAJIAN SOSIOLINGUISTIK - Munandar, Amirul; Fadli, Bagus Muhammad; Yani, Muhammad (STKIP Harapan Bima, 2025)
This study aims to examine the Indonesian language use among millennials on social media from a sociolinguistic perspective. The main focus is on code-mixing and slang expressions found in digital posts and their function in online communication. The study applies a mixed-methods approach by distributing questionnaires to 200 respondents and analyzing 30 social media posts. The results reveal that code-mixing and slang are widely used as a means of self expression, group identity, and adaptation to digital culture. The average questionnaire scores show a strong tendency toward comfort and effectiveness in using informal language. Textual analysis also indicates that social, emotional, and symbolic factors influence millennials’ language choices. The study concludes that millennials’ use of Indonesian on social media reflects a complex linguistic dynamic oriented toward social functions in the digital ecosystem.